Large retroperitoneal lymphadenopathy and increased risk of venous thromboembolism in patients receiving first‐line chemotherapy for metastatic germ cell tumors: A study by the global germ cell cancer group (G3). (12th November 2019) - Tran, Ben; Ruiz‐Morales, Jose M.; Gonzalez‐Billalabeitia, Enrique; Patrikidou, Anna; Amir, Eitan; Seidel, Christoph; Bokemeyer, Carsten; Fankhauser, Christian; Hermanns, Thomas; Rumyantsev, Alexey; Tryakin, Alexey; Brito, Margarida; et al.
Abstract: Background: Metastatic germ cell tumor (mGCT) patients receiving chemotherapy have increased risk of life‐threatening venous thromboembolism (VTE). Identifying VTE risk factors may guide thromboprophylaxis in this highly curable population. Methods: Data were collected from mGCT patients receiving first‐line platinum‐based chemotherapy at 22 centers. Predefined variables included International Germ Cell Cancer Collaborative Group (IGCCCG) risk classification, long‐axis diameter of largest retroperitoneal lymph node (RPLN), Khorana score, and use of indwelling vascular access device (VAD). VTE occurring at baseline, during chemotherapy and within 90 days, was analyzed. Results: Data from 1135 patients were collected. Median age was 31 years (range 10‐74). IGCCCG risk was 64% good, 20% intermediate, and 16% poor. VTE occurred in 150 (13%) patients. RPLN >3.5 cm demonstrated highest discriminatory accuracy for VTE (AUC 0.632, P  < .001) and was associated with significantly higher risk of VTE in univariable analysis (22% vs 8%, OR 3.0, P  < .001) and multivariable analysis (OR 1.8, P  = .02). Other significant risk factors included, Khorana score ≥3 (OR 2.6, P  = .008) and VAD use (OR 2.7, P  < .001). Conclusions: Large RPLN and VAD use are independent risk factors for VTE in mGCT patients receiving chemotherapy. VAD use should be minimized in this population and thromboprophylaxis might be considered for large RPLN. Abstract : Venous thromboembolism can cause morbidity in germ cell tumor patients receiving chemotherapy; large retroperitoneal lymphadenopathy (RPLN) and indwelling vascular access devices (VAD) are significant VTE risk factors. VAD insertion should be avoided and thromboprophylaxis can be considered for large RPLN.